Fencing statistical analysis system of On-The-Spot technical research - Zhao, C.; Ma, D.; Zhang, H.; Wang, J. (International Journal of Sports Science and Engineering, 2010)
This paper introduces the technical approach statistic analysis of fencing match the design thought, system function structure and application characteristics, the system adopts the characteristics of c + + Builder + SQL database, in Win-xp system development and design, with the interface is simple and convenient operation, the statistical results visualization features.